ANALISIS IMPLEMENTASI MODEL PROJECT BASED LEARNING (PjBL) DALAM PEMBELAJARAN TEKS NEGOSIASI DI KELAS X DKV - Holifah Holifah; Aisya Servia; Warda Sakiya; Mujahidah Fitria (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Learning negotiation texts in vocational high schools requires not only conceptual understanding but also the ability to apply text structure and linguistic features through active learning experiences. The learning situation in Class X of SMKN 1 Omben indicated that students' participation in classroom activities still needed to be strengthened, making it necessary to adopt an instructional approach capable of connecting theoretical understanding with authentic learning experiences. In this context, the implementation of Project-Based Learning (PjBL) was examined to explore how the model was carried out, how students responded throughout the learning process, and how their learning outcomes changed following project-based activities. This study employed a qualitative descriptive approach. Data were collected through classroom observations, interviews with teachers and students, and documentation of students' project work. The data were subsequently organized, analyzed, and interpreted to obtain a comprehensive understanding of the instructional process. The findings revealed that PjBL was implemented through four stages: project planning, project implementation, presentation, and evaluation. Throughout these stages, students actively participated in discussions and collaborative group work, successfully produced negotiation texts that conformed to the required structural and linguistic conventions, and demonstrated improved understanding of text structure, persuasive language use, and the ability to present logical arguments. Overall, the implementation of Project-Based Learning was conducted effectively, creating a more participatory learning environment in which students successfully completed their assigned projects in accordance with the intended learning objectives. ABSTRAK Pembelajaran teks negosiasi di sekolah menengah kejuruan tidak hanya menuntut penguasaan konsep, tetapi juga kemampuan menerapkan struktur dan kaidah kebahasaan melalui aktivitas belajar yang melibatkan siswa secara aktif. Kondisi pembelajaran di kelas X SMKN 1 Omben menunjukkan bahwa keterlibatan peserta didik dalam proses belajar masih perlu ditingkatkan sehingga diperlukan pendekatan yang mampu menghubungkan pemahaman materi dengan pengalaman belajar nyata. Dalam konteks tersebut, penerapan Project Based Learning (PjBL) dikaji untuk melihat bagaimana model ini dijalankan, bagaimana respons siswa selama pembelajaran berlangsung, serta bagaimana perubahan hasil belajar yang ditunjukkan setelah kegiatan berbasis proyek dilaksanakan. Penelitian menggunakan pendekatan deskriptif kualitatif dengan memanfaatkan observasi, wawancara terhadap guru dan siswa, serta dokumentasi proyek sebagai sumber data. Analisis dilakukan melalui tahapan pengumpulan, pengolahan, dan penafsiran data hingga diperoleh gambaran utuh mengenai proses pembelajaran. Temuan penelitian memperlihatkan bahwa pembelajaran berlangsung melalui tahap perencanaan proyek, pelaksanaan, presentasi hasil, dan evaluasi. Selama setiap tahapan tersebut, siswa terlibat aktif dalam diskusi dan kerja sama kelompok, mampu menghasilkan teks negosiasi yang sesuai dengan struktur dan kaidah kebahasaan, serta menunjukkan peningkatan pada pemahaman struktur teks, penggunaan bahasa persuasif, dan penyampaian argumen secara logis. Keseluruhan proses implementasi PjBL berlangsung dengan baik sehingga pembelajaran menjadi lebih partisipatif dan seluruh tugas proyek dapat diselesaikan sesuai tujuan yang telah ditetapkan.